Mastering Autodesk Maya 2016 - Palamar, Todd (John Wiley& Sons, 2016)
Go from 'beginner' to 'expert' with this professional, tutorial-based guide to Maya 2016 Mastering Autodesk Maya 2016 is your professional hands-on coverage to getting the most out of Maya. If you already know the basics of Maya, this book is your ticket to full coverage of all Maya 2016's latest features, and showcases the tools and methods used in real-world 3D animation and visual effects. From modeling, texturing, animation, and effects to high-level techniques for film, television, games, and more, this book expands your skill set, and helps you prepare for the Autodesk Maya certification